Evaluation of the dorsal curvature in elderly women by means of the index of thoracic kyphosis (Fisioterapia e Pesquisa, 2006)
Thoracic kyphosis is a physiological convexity of the spine that may increase due to muscular-skeletal alterations or in advanced age. This study aimed at evaluating alterations of the thoracic kyphosis in women over 60, comparing results obtained with standard values pointed to by literature. The study involved 72 women over 60, divided into 5-year categories. Two examiners assessed the thoracic kyphosis by using a flexible ruler and moulding the spine curvature between the 7th cervical and 2nd sacral vertebrae. Measures taken by the two examiners were compared by the intraclass correlation coefficient (ICC); the index of thoracic kyphosis (ITK) was calculated for each woman. Possible associations between age, kind of work and the ITK were searched for. Results showed: strong reproducibility (ICC=0.85; the 60-to-64 age group presented the largest proportion of assessed subjects (31.9%) and the greatest proportion of ITK alterations (45.1%) when compared to standard values; no relation could be established between normal and altered values, and age or work. The method proved to be non=invasive, simple and a low-cost one. Less than 50% of the sample presented ITK alterations.